Art Brut Music Studio / Tengku Ahmad Faizal Tengku Majid… [et al.] - Tengku Majid, Tengku Ahmad Faizal; Ahmad Tamizi, Ahmad Musahimi; Mohamad Kamil, Mohamad Izzuddin; Mohd Said, Mohd Amirul (2010)
The ART BRUT Music Studio Enterprise is a company which fully owned by Bumiputera, provide services of jamming session, song recording, music lesson and musical instrument rental to the customers around in Pulau Pinang, Kulim and Sungai Petani. This company is located at 485, Lorong Perda Utama 9, Bandar Perda, 14000 Bukit Mertajam, Pulau Pinang. It has its own opportunity to exist in music based business industry, where there are not many such businesses existed in Pulau Pinang. This advantage would lead the company growth well with strong base to stand and will animate the local music industry. ART BRUT Music Studio is under partnership business form. It was participated by four members, which are Mr. Ahmad Musahimi Bin Ahmad Tamizi as General and Administration Manager, Tengku Ahmad Faizal bin Tengku Majid as Marketing Manager, Mr. Mohamad Izzussin bin Mohamad Kamil as Financial Manager, and last but not least Mr. Mohd Amirul bin Mohd Said as Operation Manager. The company capital is RM 175,000.00. Three of the partners contributed equally, RM 35,000.00 and Mr. Ahmad Musahimi bin Ahmad Tarmizi contributed RM70,000.00. Based from the survey which had been conducted, it was found out that the company location is strategic because of there is not many such business in Bandar Perda while the customers demand is quite high. Compare to another competitors those have already located in there, they’re only provide jamming session service neither song recording nor instrument rental. To fulfil the customers need, our company had provided extra services instead jamming session as an advantage. The business concept is family entertainment centre and targeting customers is not limited.